Research on teachers' level of trust to the collegues, the students and the parents - Bilgic, Ozlem; Gumuseli, Ali Ilker (ELSEVIER SCIENCE BV, 2012)
Schools are the most important organizations of society. The success and efficiency of schools depend mostly on the trust between and among teachers, students and parents. Lack of trust in colleagues, students and parents damages the relations between them and prevents cooperation at schools. In a short period of time, building trust at schools will improve the quality of the relationships between teachers, students and parents. In a long period of time, it may pave the way for improvements which will affect the whole society. Thus, it is important to detect teachers' level of trust towards their colleagues, the students and the parents and measures that need to be taken to increase the level of trust among stakeholders. In this study, some conclusions that and the are drawn from the investigations of the elementary school teachers' level of truxst towards their colleagues, the students parents and some factors that affect their beliefs will be presented. This research was carried out within the framework of the general research model. The study population included 2857 teachers employed in 57 public elementary schools in the 2010-and the rest 334 (41.9%) were men from 24 different elementary schools. Data of the research were gathered through the based on the Trust Scale (T Scale) of Hoy and Tschannen-Moran was used in this research.. the parents and the students are ranked respectively. Yet, it has also been found out that there is a significant correlation between the level of trust towards the students and parents and professional seniority and the number of teachers at school. Besides, there is also a significant correlation between the level of trust towards the colleagues and seniority. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Organizational trust; trust; elementary school education; Education & Educational Research